Δ6 FATTY ACYL DESATURASE GENE IN A SOUTHERN BLUEFIN TUNA (Thunnus maccoyii) CELL LINE - Senni Juniawati Bunga; Kathy Schuller (The East Java Biological Society, 2015)
Fish is the main source of ω-3 long chain polyunsaturated fatty acids (LC-PUFA) such as eicosapentaenoic acid (EPA, 20:5ω-3) and docosahexaenoic acid (DHA, 22:5ω-3), which have positive effects on human health and can be beneficial in human diet context. Studies involving fatty acyl desaturase (Fads) and elongase of very long chain fatty acids (Elovl) enzymes that convert C18 PUFA to C20/22 LC-PUFA have been performed in some fish species. However, very little is known about LC-PUFA biosynthesis in tuna species. This study investigated the Δ6 Fads gene performance in the SBT cell line. The Δ6 Fads nucleotide sequences from various fish species were identified and retrieved to compare them with the SBT Δ6 Fads nucleotide sequence. The Δ6 Fads gene was performed using real time PCR (RT-PCR) and then was compared it with β-actin gene performance as a reference housekeeping gene. By performing multiple sequence alignments and comparing the highly conserved regions among fish Δ6 Fads sequences, the SBT Δ6 Fads nucleotide sequence was determined to be ≥ 75% identical to the other fish Δ6 Fads sequences. The results showed that when the SBT Δ6 Fads and β-actin cDNAs were performed in a standard PCR system and the products were analysed by electrophoresing them on a 2% (w/v) agarose gel, the target genes that were obtained were similar to the expected sizes. The observed band size for the Δ6 Fads PCR product was 207 bp and for the β-actin PCR product was 98 bp. The presence of the observed bands indicated that the primer pairs that were designed and used were successfully amplified the target genes. The results of this study might provide relevant information to support further investigating of the desaturase and elongase gene expression that might contribute to a better understanding of ω-3 LC-PUFA biosynthesis in fish.